Prevalence of chronic kidney disease and associated factors among adult diabetic patients: a hospital-based cross-sectional study - Aregawi, Kibrom; Kabew Mekonnen, Getachew; Belete, Rebuma; Kucha, Winner (Frontiers in Epidemiology, 2024)
Background: Chronic kidney disease is recognized as having a significant impact on public health with a high morbidity and death rate. Most diabetic patients, in the course of their lives, develop diabetic kidney disease. In the least developed nations, its size is outstripping itself. This study aimed to determine the prevalence of chronic kidney disease and associated factors among adult diabetic patients.A hospital-based cross-sectional study was conducted on 328 adult diabetic patients from December 1, 2023 to April 4, 2024 at Ayder Comprehensive Specialized Hospital, northern Ethiopia. A systematic random sampling method was utilized to select study participants.Pretested structured questionnaires were used to collect sociodemographic, economic, and behavioral/lifestyle factors. Medical records were also reviewed to collect clinical data.Creatinine analysis was performed by kinetic alkaline picrate method and Chronic Kidney Disease Epidemiology Collaboration 2021 equation was used to calculate the glomerular filtration rate from the serum creatinine, age, and sex. Proteinuria was determined by the dipstick semi quantitative method. Data was entered and analyzed using SPSS version 29. A variable with a p-value of < 0.25 in bivariate logistic regression analyses was analyzed in multivariate logistic regression to identify the associated factors. In multivariable logistic regression, a variable was deemed statistically significant if it had a p-value of less than 0.05. Associations were presented as odds ratio along with 95% confidence intervals.The prevalence of chronic kidney diseases in adult diabetic patients was 26.5% (95% CI, 21.8-31.7%). By stage, about 5.2% had stage one, 12.5% had stage two, 7.3%, 0.9%, and 0.6% had stages three, four, and five chronic kidney diseases, respectively. Hypertension (AOR=2.390 95% CI, (1.394 -4.099), p=0.002), > 10-year duration of diabetes (AOR = 2.585; 95% CI, 2.321 -5.807; P = 0.001), and family history of kidney diseases (AOR = 2.884; 95% CI, 1.338 -6.218; P = 0.007) were associated factors of chronic kidney diseases.The study revealed that one in four diabetic patients had chronic kidney disease. Special attention should be given to patients with family history of CKD, long duration on diabetes and concomitant hypertension.